Predictive value of hyperreflective foci for anti-VEGF therapeutic outcomes in different subtypes of diabetic macular edema: a retrospective analysis - Wang, Yalin; Li, Fengjiao; Hao, Miao; Kong, Xianxian; Zhou, Weiyan (Frontiers in Endocrinology, 2025)
ObjectiveTo analyze the correlation between optical coherence tomography (OCT) biomarkers and therapeutic outcomes in patients with different subtypes of diabetic macular edema (DME) following anti-VEGF treatment.MethodsA retrospective analysis was conducted on 113 patients diagnosed with DME and treated with intravitreal anti-VEGF therapy. Based on OCT characteristics, patients were categorized into three groups: cystoid macular edema (CME), diffuse retinal thickening (DRT), and serous retinal detachment (SRD). The primary outcome measures were the best-corrected visual acuity (BCVA), central macular thickness (CMT) and the number of hyperreflective foci (HRF) at each follow-up time point during the observation period. The secondary outcome measures included the status of other OCT biomarkers such as disorganization of retinal inner layers (DRIL), the inner segment/outer segment (IS/OS) disruption, and hard exudates at baseline. Additionally, the relationship between HRF, CMT and BCVA was analyzed.ResultsThe CME group had the worst BCVA (LogMAR) throughout (vs. DRT/SRD, all P<0.05), while DRT and SRD showed no significant difference (all P>0.05). For HRF, the DRT group had the fewest HRF across retinal layers from baseline to the end of follow-up (e.g., inner retina: 1.91 ± 1.22 at 12 months, ANOVA P<0.001; post-hoc: DRT vs. CME P<0.001, DRT vs. SRD P<0.001). The CME group exhibited the great reduction in HRF (inner retinal layer: -2.53 ± 2.14 vs. -1.07 ± 1.44 in DRT, P = 0.001; -2.36 ± 2.34 in SRD, P = 0.457) but recurrence at 6 months (351.78 ± 110.93 μm at 6 months vs. 330.03 ± 94.94 μm at 3 month). The SRD group maintained the highest HRF number, especially in outer retina (e.g., outer retinal layer: 1.97 ± 1.81 at 12 months vs. 0.66 ± 0.99 in DRT, P<0.001; 1.47 ± 0.97 in CME, P = 0.109). The DRT group had the lowest CMT at baseline (ANOVA P<0.001; post-hoc: DRT vs. CME P<0.001, DRT vs. SRD P<0.001). At 6 months, differences were mainly between DRT and CME (ANOVA P = 0.017; post-hoc: p=0.006). The SRD group showed the least CMT change from baseline to final follow-up (ANOVA P<0.001; post-hoc: DRT vs. CME P<0.001, DRT vs. SRD P<0.001). Binary logistic regression identified baseline CMT (β=0.012, 95%CI 1.000–1.024, P = 0.043), inner HRF (β=–0.712, 95%CI 0.238–1.011, P = 0.047), and outer HRF (β=–0.797, 95%CI 0.375–1.083, P = 0.031) as independent predictors of visual prognosis.ConclusionAnti-VEGF therapy can reduce the number of HRF in the three subtypes of DME. Baseline HRF, especially within the inner and outer retinal layers, are useful prognostic markers for visual acuity. Subtype-specific treatment and monitoring approaches may enhance long-term visual prognosis in DME patients.